2020
DOI: 10.1194/jlr.tr119000468
|View full text |Cite
|
Sign up to set email alerts
|

Lipid rafts in glial cells: role in neuroinflammation and pain processing

Abstract: Activation of microglia and astrocytes secondary to inflammatory processes contributes to the development and perpetuation of pain with a neuropathic phenotype. This pain state presents as a chronic debilitating condition and affects a large population of patients with conditions like rheumatoid arthritis and diabetes, or after surgery, trauma, or chemotherapy. Here, we review the regulation of lipid rafts in glial cells and the role they play as a key component of neuroinflammatory sensitization of central pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 145 publications
1
85
0
Order By: Relevance
“…AIBP plays a unique role of targeting cholesterol efflux machinery to TLR4-occupied inflammarafts [ 10 , 11 ]. Evidence from clinical and animal studies indicates that TLR4-dependent signaling is an important factor in the pathogenesis of POAG and that this signaling is associated with activated glial cells and contributes to inflammatory responses in experimental glaucoma [ [43] , [44] , [45] ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…AIBP plays a unique role of targeting cholesterol efflux machinery to TLR4-occupied inflammarafts [ 10 , 11 ]. Evidence from clinical and animal studies indicates that TLR4-dependent signaling is an important factor in the pathogenesis of POAG and that this signaling is associated with activated glial cells and contributes to inflammatory responses in experimental glaucoma [ [43] , [44] , [45] ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, accumulating evidence suggests that damage-associated molecular patterns (DAMPs) which are endogenous activators of TLR4 released by damaged cells activate microglia and produce inflammatory cytokines [ 10 , 93 ]. The activated microglia-mediated neuroinflammation is an early event in glaucoma, leading to Müller glia activation, neuronal damage, and RGC loss [ 94 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further understand the basis of these effects, we aimed at deciphering the molecular mechanisms involved in resveratrol neuroprotection. It was shown that resveratrol could enter the cell by endocytosis via lipid rafts ( Delmas et al, 2013 ; Neves et al, 2016 ), which are present on the plasma membranes of both neurons ( Tsui-Pierchala et al, 2002 ) and astrocytes ( Miller et al, 2020 ). However, once inside the cell, its mode of action is far from being fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…When TLR4 is activated, a large number of cytokines, chemokines, and lipids are secreted. These products act on receptors of spinal dorsal horn neurons, enhance pain signaling, and produce hyperalgesia [ 78 ]. Blocking HMGB1-TLR4 signaling in the spinal cord of collagen antibody-induced arthritis (CAIA) mice can reverse the mechanical hypersensitivity in the inflammatory stage and late stage of the model [ 50 ].…”
Section: Toll-like Receptors (Tlrs)mentioning
confidence: 99%